Outcome-Based Education Model: Its Impact and Implications for Lecturer Creativity and Innovation in Higher Education - Asbari, Masduki; Novitasari, Dewiana (International Journal of Social and Management Studies, 2024)
This study examines the impact of Outcome-Based Education (OBE) on fostering creativity and innovation among lecturers in higher education, focusing on curriculum design, teaching methods, and assessment practices. Through a qualitative descriptive approach, including key informant interviews, observations at a university in Tangerang, and literature review, this research explores lecturers' experiences and challenges in adapting to an outcome-oriented educational model. The findings reveal that OBE encourages lecturers to develop more engaging and practical curricula, allowing them to integrate creative and student-centered teaching methods. It also supports the implementation of innovative assessment techniques, including project-based and collaborative evaluations, which provide a more comprehensive understanding of students' abilities. Despite these benefits, lecturers face challenges related to time management, resource constraints, and the need for professional development, highlighting the importance of institutional support and a collaborative culture in successful OBE implementation. This study contributes to existing literature by providing insights into the specific conditions necessary for OBE success and implications for policy and practice in higher education, suggesting pathways for future research to expand OBE's adaptability and effectiveness.